Ranking by competence using a fuzzy approach - Suleman, A.; Suleman, F. (Quality and Quantity, 2012)
New approaches in economics of education consider the concept of competence to bringing in the multidimensional feature of labour force quality. Competence includes knowledge, skills, behaviours and attitudes. Each individual suits the combination of these elements to perform a task. Thus, different combinations expectedly lead to different task performance inside an occupation. In this paper, we focus on individual heterogeneity in homogeneous job requirements context. In sequel, we establish a theorem on unit simplex that potentially provides a ranking system by competence. The system is designed under a grade of membership framework, with a technique based on fuzzy sets theory. Under certain conditions, the referred theorem allows a mapping of individual multidimensional feature into the interval [0, 1]. So, the greater the value along this interval, the more competent the individual. An empirical study of a banking sector activity illustrates our research.